Quality of Life and Symptom Burden With First- and Second-generation Tyrosine Kinase Inhibitors in Patients With Chronic-phase Chronic Myeloid Leukemia - BOSTAN, HAYRİ; ATAGÜNDÜZ, IŞIK; TOPTAŞ, TAYFUR (CIG MEDIA GROUP, LP, 2020)
We assessed the quality of life and symptom burden in patients with chronic-phase chronic myeloid leukemia (CML) receiving first- or second-generation tyrosine kinase inhibitors, to demonstrate whether there are differences between tyrosine kinase inhibitor generations. A total of 121 patients with CML with good performance and low comorbidity scores were enrolled in the study. Similar results were observed between the groups in the quality of life and symptom burden scores, which were examined using CML-specific (European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire-Chronic Myeloid Leukemia module, MD Anderson Symptom Inventory for Chronic Myeloid Leukemia) questionnaires. Background: With the advent of tyrosine kinase inhibitors (TKIs), patients with chronic myeloid leukemia (CML) have a life expectancy similar to those of age- and gender-matched healthy populations. Nevertheless, patients receiving TKIs report chronic adverse events such as fatigue, edema, and muscle cramps, which lead to a decrease in their quality of life (QoL). Therefore, the aim of this study was to assess the QoL and symptom burden in patients receiving original imatinib, generic imatinib, dasatinib, and nilotinib. Patients and Methods: A total of 121 patients with CML who received TKIs for at least 3 months were enrolled in the study. The QoL was assessed with the Organisation for Research and Treatment of Cancer Quality of Life Questionnaire-Core 30 (EORTC QLQ-C30) and Quality of Life Questionnaire-Chronic Myeloid Leukemia (QLQ-CML24) modules. The symptom burden was assessed with MD Anderson Symptom Inventory for Chronic Myeloid Leukemia (MDASI-CML) and EORTC QLQ-CML24. Results: The median age of the study population was 53 years (range, 28-90 years), and 83 (81.4%) patients had a low-to-medium Sokal risk score. The Eastern Cooperative Oncology Group performance status of most patients were good (< 2; 96%), and comorbidity scores were low (HCT-CI < 3; 90.8%). There was no significant difference between the general health status of patients in terms of EORTC QLQ-C30 and QLQ-CML24. According to the results of the MDASI-CML and QLQ-CML24 modules, the most common symptom was fatigue (58.7%) in all groups, and there were no significant differences between the groups in terms of the effects on the daily life activities of the patients. Conclusion: Patients with CML receiving first- and second-generation TKIs were seen to have a similar QoL and symptom burden. (C) 2020 Elsevier Inc. All rights reserved.
Keywords: CML; Dasatinib; Generic imatinib; Imatinib mesylate; Nilotinib; EUROPEAN-ORGANIZATION; CANCER QLQ-C30; IMATINIB; OUTCOMES; NILOTINIB; THERAPY